Pengaruh Pendidikan Kesehatan Dengan Metode Simulasi Pertolongan Pertama (Log Roll) Pada Korban Dengan Indikasi Cedera Tulang Belakang Di Pendidikan Informal Kecamatan Tempuran Magelang - Akhmad Rifai; Moh Ilyas (Poltekkes Kemenkes Surakarta, 2019)
Background: Prevalence in Indonesian society in 2007 was 7.5%, with several factors causing traffic and crossing sharp/ blunt objects. In 2013 there was an increase in the prevalence of trauma to 8.2%, with the highest order of injuries being down 40.9%, motorcycle accidents (40.6%), trauma due to sharp/blunt objects 7.3%, other land transportation 7, 1% and 2.5% fallout. To equip ordinary students in carrying out the Log roll Skills to help victims with spinal trauma need to do log roll Skills training. In this regard, researchers intend to conduct research on